2008
DOI: 10.1094/phyto-98-11-1205
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variability of Cercospora coffeicola from Organic and Conventional Coffee Plantings, Characterized by Vegetative Compatibility

Abstract: Cercospora leaf spot is a destructive fungal disease that has become a threat to the coffee industry in Brazil. Nevertheless, little is known about populations of its causal agent, Cercospora coffeicola. We evaluated the potential of using nitrogen-nonutilizing (nit) mutants and vegetative compatibility groups (VCGs) to characterize the genetic variability of the C. coffeicola population associated with coffee plantings in Minas Gerais state (MG), Brazil. A total of 90 monosporic isolates were obtained from sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…Although the 60 coffee isolates originated from three geographic regions and two production systems, their variability was not related to either the region or cropping system. A high variability of C. coffeicola , as it relates to vegetative compatibility, was also reported (Martins et al. 2008), but it was suggested that the variability was not due to the effect of the geographic region or cropping system because coffee is continuously planted throughout Minas Gerais and C. coffeicola is wind dispersed.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Although the 60 coffee isolates originated from three geographic regions and two production systems, their variability was not related to either the region or cropping system. A high variability of C. coffeicola , as it relates to vegetative compatibility, was also reported (Martins et al. 2008), but it was suggested that the variability was not due to the effect of the geographic region or cropping system because coffee is continuously planted throughout Minas Gerais and C. coffeicola is wind dispersed.…”
Section: Discussionmentioning
confidence: 96%
“…To assess the variability, a thorough study was conducted in Minas Gerais, the largest coffee‐producing state in Brazil, and the distribution pattern of vegetative compatibility groups of C . coffeicola isolates, collected in conventional and organic coffee fields from three geographic regions of Minas Gerais State, was used to infer the variability in the pathogen populations (Martins et al. 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Moretti et al, 2004(Moretti et al, , 2006Groenewald et al, 2008), C. canescens Ellis & Martin (Joshi et al, 2006), C. coffeicola Berk. & Cooke (Martins et al, 2008), and C. kikuchii (Matsumoto & Tomoy.) Gardner (Almeida et al, 2005;Cai & Schneider, 2005;Lura et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Asexual processes such as vegetative compatibility, parasexual recombination, and mutation also should be considered as possible reasons for the high level of genetic diversity in C. sojina, since no sexual stage has been identified for this fungus. Vegetative compatibility has been demonstrated in other species of Cercospora, such as C. kikuchii and C. coffeicola (Cai & Schneider, 2005;Martins et al, 2008), and additional research should be conducted to investigate vegetative compatibility in C. sojina.…”
Section: Resultsmentioning
confidence: 99%